Formation of key skills of the XXI century in the educational practice of a teacher - Beissembayeva, Saltanat; Oshakbayeva, Zhanar; Yerkibayeva, Gulfairuz; Babayeva, Karlygash; Chakanova, Selime (Institute of Advanced Engineering and Science, 2025)
This study addresses the pressing need to develop key XXI century skills among teachers to effectively navigate the contemporary educational challenges that they are facing. Through interviews with 86 educators from Kazakh pedagogical universities, we identified several essential competencies, including digital literacy, critical thinking and collaboration, as being fundamental for successful teaching in modern contexts. The research proposes a multifaceted approach, employing innovative strategies such as active learning, project-based learning, and collaborative techniques, to seamlessly integrate these skills into the curriculum. The findings indicate that these methods not only enhance students’ practical experiences but also foster a supportive learning environment conducive to creativity and effective problem-solving. The study concludes by emphasizing the vital role of continuous professional development for teachers, ensuring they can adapt their pedagogical practices in response to the rapidly evolving demands of education today.